2022
DOI: 10.3390/buildings12050630
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Characteristics of Fireproof Plaster Compositions in Exposure to Various Regimes of Fire

Abstract: The problems of the fire safety of oil and gas facilities are particularly relevant due to the increasing complexity of technological processes and production. Experimental studies of steel structures with three different types of plasters are presented to determine the time taken to reach the critical temperature and loss of bearing capacity (R) of the sample, as a result of reaching a rate of deformation growth of more than 10 mm/min and the appearance of the ultimate vertical deformation. The simulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…With sensitive mixing, and when the correct consistency of the mixture was found that avoided crushing the expanded perlite, a bulk density of 587 kg/m 3 was achieved in the wet state. This wet bulk density was similar to that of industrial fire plaster (Gravit et al ., 2022; Kiran et al ., 2022).…”
Section: Sample Preparationsupporting
confidence: 81%
“…With sensitive mixing, and when the correct consistency of the mixture was found that avoided crushing the expanded perlite, a bulk density of 587 kg/m 3 was achieved in the wet state. This wet bulk density was similar to that of industrial fire plaster (Gravit et al ., 2022; Kiran et al ., 2022).…”
Section: Sample Preparationsupporting
confidence: 81%
“…SP ELCUT has been repeatedly used to solve thermophysical problems to verify by comparing the results obtained with experimental data. For example, Gravit and co. [37] conducted experimental studies and simulation in SP ELCUT of steel structures with three different types of plaster. Simulation of the heating of steel structures showed good correlation with the experimental results and allowed to predict the consumption of plastering compound for a sample steel column.…”
Section: Simulation Of Fire Curtains Canvasmentioning
confidence: 99%
“…It is assumed that the foam coke is uniformly distributed over the column in time. This approach is not analogous to the behavior of plaster compositions when the simulation is divided into three parts: before, during and after the phase transition of water to vapor (evaporation), which takes place on the heating curve at about 100 • C, with the duration of this phase in time depending on the moisture content of the material [40]. Foam coke formation generally occurs from the 3rd minute of fire exposure and is completed in an average of 15-20 min.…”
Section: Introductionmentioning
confidence: 99%